Plus Dolor and Nuevo Negro: Gustavo Urrutia and his work in the Black/Afro-descendant press in Cuba (Anclajes, 2025)
The presence of Blacks/Afro-descendants in the Latin American intellectual field can be observed through their participation in periodical publications, not only as authors of texts that discuss current events or deploy analytical and categorical proposals, but also as editors of their own newspapers and magazines, which focus on a reading public that recognizes itself as Black/Afro-descendant. This is the case of the Afro-Cuban intellectual Gustavo Urrutia, who, in the first half of the 20th century used the press, especially the Black/Afro press, to spread concepts such as Plus Dolor and Nuevo Negro. The text begins with a review of the term Black/Afro press and its development in Cuba, as well as Urrutia’s role in this context. It proceeds to analyze the mentioned categories, considering their publication spaces, the author’s construction of each one, and their conceptual influences. The text concludes with an evaluation of Urrutia’s place and his proposals in the trajectory of Black/Afro thought in Latin America and the Caribbean.
Keywords: Gustavo Urrutia; African Americans; Latin American Press; Cuba; 20th Century